Posthumous homosexualities: Queer poetics in Sonnets of dark love by Federico García Lorca - La Madrid Vivar, Pablo Lenin (2022)
The essay examines the queer lyrical creation of the Spanish poet Federico García Lorca through the interpretation of the eleven poems that make up the book Sonnets of dark love. Sonnets that constitute the queer poetry of Lorca, who began to write them in 1935, but which were officially published posthumously in 1984 in the ABC newspaper in Madrid. Sonnets of dark love has as its central theme the passionate love that Lorca felt for his lover Rafael Rodríguez Rapún and, according to Manuel Francisco Reina, also dedicated to Juan Ramírez de Lucas. Federico García Lorca's homosexuality brought him sorrow throughout his life, knowing this he hides his homosexual love in order to avoid the shame of a conservative and homophobic society that implies humiliation and exclusion. However, this discriminatory society cannot end the amatory feelings of the poet who uses queer poetry to sing to his hidden lovers.